1993
DOI: 10.1093/cvr/27.9.1613
|View full text |Cite
|
Sign up to set email alerts
|

The endothelin-1 receptor antagonist BQ-123 reduces infarct size in a canine model of coronary occlusion and reperfusion

Abstract: These data indicate that endothelin-1 release during ischaemia may be involved in the pathogenesis of myocardial ischaemia and infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0
2

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(56 citation statements)
references
References 0 publications
3
51
0
2
Order By: Relevance
“…Studies in isolated hearts showed that ET-1 release increases on early reperfusion after ischemia, thereby contributing to injury (7), and that ET-1 is a major factor that depresses cardiac function (6) and causes cell necrosis (8). These findings are consistent with other studies (21,23,30) demonstrating a relationship between ET-1 and the pathogenesis of myocardial ischemia. In humans, acute hypertriglyceridemia stimulates ET-1 release in normal subjects (36).…”
supporting
confidence: 86%
“…Studies in isolated hearts showed that ET-1 release increases on early reperfusion after ischemia, thereby contributing to injury (7), and that ET-1 is a major factor that depresses cardiac function (6) and causes cell necrosis (8). These findings are consistent with other studies (21,23,30) demonstrating a relationship between ET-1 and the pathogenesis of myocardial ischemia. In humans, acute hypertriglyceridemia stimulates ET-1 release in normal subjects (36).…”
supporting
confidence: 86%
“…Endothelin levels are elevated in patients with congestive heart failure, hypertension, and postmyocardial infarction and contribute to myocardial ischemic-reperfusion injury (12,32,38). Understanding the mechanism by which vasodilators counter endothelin-induced vasoconstriction may aid in developing pharmacological tools to counter the pathophysiological effects of endothelin.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Grover et al reported that BQ-123 had no effect on regional myocardial blood flow in ischemic and non-ischemic tissue [34].…”
Section: Discussionmentioning
confidence: 98%